(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Financial management is all about monitoring, controlling, protecting, and reporting on a company’s financial resources. Companies have accountants or finance teams responsible for managing their finances, including all bank transactions, loans, debts, investments, and other sources of funding.